Calculating the inventory of an item with normal demand and exponential delivery time - Izar Landeta, Juan Manuel; Nájera Saldaña, José Adrián; Zárate Camacho, Lizbeth Angélica (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To study the case of calculating the inventory of an item with normal demand and exponential supplier delivery time.MATERIAL AND METHOD: Traditional order quantity and reorder point models are applied through simulation, including savings from purchasing larger volumes.RESULTS: The order quantity and reorder point were obtained for the illustrative case, and then the word-of-mouth effect and standard deviation of demand were varied. As these two parameters increase, so does inventory cost, with the change in cost being practically linear with the standard deviation.CONCLUSIONS: The order quantity was within the lower limits of maximum volume, 5,001 and 10,001 items. As the word-of-mouth effect increased, the cost of shortages and inventory, as well as the order quantity, increased. With a higher standard deviation, inventory costs increased linearly, even increasing the reorder point.Among the limitations of the study is that a probability distribution was used for the supplier's demand and delivery time, which allows for the use of other probability distributions in future cases.
Keywords: order quantity; reorder point; inventory cost; demand; lead time.